PENGARUH HARGA CPO DAN NILAI TUKAR USD/IDR TERHADAP KEWAJIBAN BUNGA NASABAH SEGMEN KORPORAT PERUSAHAANINDUSTRI CPO DAN TURUNANNYA DI BANK MANDIRI - , Faisal Fahri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
CPO is a commodity which has now become the primary needs of the wide community both in terms of benefit and utilization. The utilization of CPO covers almost all aspects in life starting from food, cosmetics, healthcare to fuel vehicles. In addition, this commodity is categorized as an environmental-friendly commodity, given palm oil as the raw materials is a crop that can always be re-planted, thus providing higher added value than the crude oil as well as an alternative to crude oil commodities (substitutes). In relation to the above conditions, CPO becomes a very attractive commodity to be traded both domestically and internationally, which makes the demand for this commodity in the market is always high. As a commodity that is consumed globally, generally palm oil is traded in USD. The attractiveness of CPO industry becomes one of the considerations for most banks in providing a range of banking products and services to its perpetrators, one of the many banking products given by PT Bank Mandiri (Persero) Tbk to the palm oil-based industry is Working Capital Facility. PT Bank Mandiri (Persero) Tbk is one of the National Bank that has a large loan portfolio in the agriculture industry, particularly in palm oil-based industry (CPO). The exposure to the sector in the year 2011 reached to Rp. 43.6 trillion or 65% of the total loan portfolio in agriculture industry or 12% of total outstanding loans PT Bank Mandiri (Persero) Tbk. CPO commodity in the downstream business is one of the main raw materials, so that the CPO price changes and fluctuations in the exchange rate of USD / IDR expected to affect the amount of working capital required by those companies who are engaged in the palm oil industry. As an effect, it will impact on the amount of interest expenses paid for the working capital facility provided by the Bank. Considering the above matters, the principle problem of this study is whether there is an influence from the CPO industry and the CPO price changes and fluctuations in the exchange rate USD / IDR to the interest expenses paid for the working capital facility of Bank Mandiriâs corporate clients who are engaged in palm-oil industry within the year 2007 to 2011. After the analysis, the results of research carried out shows that there is no impact influenced by the CPO industry and the CPO price changes and fluctuations in the exchange rate USD / IDR to the interest expenses paid for the working capital facility of Bank Mandiriâs corporate clients who are engaged in palm-oil industry within the year 2007 to 2011. With these conditions, as a strategy, Bank Mandiri can explore to provide incentives by granting an attractive interest rate to encourage the increase utilization of the credit facilities.